Atrial natriuretic factor synthesis and storage during ontogeny of the chicken embryo heart: an immunocytochemical and ultrasfrucfural study using tannic acid as inhibitor of the exocyfosis processes - VIEIRA, ELSA FIGONI DE; Paz, Dante; Casco, Victor Hugo (Revista Ceres, 2015)
-